A theory of recognition as framework for religious education. Reading Axel Honneth from a pedagogical and theological perspective - Altmeyer, Stefan 1976- (2018)
Experiences of withheld and of granted recognition constitute an integral part of everybody's learning biography, as the experience of recognition is crucial to all processes of socialisation and identity formation. In consequence, the last two decades have seen a considerable interest in recognition theories, initially particularly in the field of political and social theory but later extending into educational contexts. In dialogue with the influential theory of recognition by German philosopher Axel Honneth, this paper develops an interpretation of recognition which can enrich the theory of education, and in particular that of religious education. A theological perspective on recognition is provided that aims to identify and specify the distinctive contribution that religious education can make to the realisation of recognition in schools and the basic implications for theory and practice that follow from this.
Keywords: Axel Honneth; Recognition; Religious Education; religious recognition